Optimizing ceramic waste content in concrete mix design: model development and android application - Andaryati, Andaryati; Suharso, Akbar Bayu Kresno; Raharja, Danang Setiya; Saurina, Nia (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2025)
There is an increasing need for practical tools that help users determine the appropriate mix composition of concrete incorporating ceramic waste as a partial fine aggregate replacement. Such tools can simplify the process of designing environmentally friendly concrete while ensuring that the resulting material meets the required strength standards. This study aims to determine the percentage of concrete mixture utilizing ceramic waste as a substitute for fine aggregates in concrete, assess its impact on concrete compressive strength using the RMSE method, and visualize it through Android modulator technology. Compressive strength tests were based on the previous research study, with curing intervals of 7, 14, and 28 days. The concrete quality test results indicate that concrete mixed with ceramic waste as a partial replacement for fine aggregates produces a strength that meets the standard for normal concrete, ranging between 30 - 40 MPa. A polynomial regression model synthesis based on the available laboratory data demonstrated good reliability, with an RMSE value of 0.172. Furthermore, using an Android emulator technology named BetonKU, the application successfully visualized the concrete mix design composition incorporating ceramic waste as a fine aggregate substitute according to the input data for the designed concrete strength.